THE NEW ABSOLUTE PARAMETERS OF OU GEM - THE STAR OF BY DRA TYPE - Mishenina, T. V.; Glazunova, L. V.; Soubiran, C.; Kovtyukh, V. V. (Одеські астрономічні публікації, 2010)
The spectra of OU Gem were obtained with the fiber-fed echelle spectrograph SOPHIE at the 1.93-m telescope of the Observatoire de Haute- Provence (France). The temperatures of components of the system were defined and are equal to 5013 ± 15 K and 4486±50 K for primary (A) and secondary (B) components, accordingly. The rotation velocity of components are measured: for primary component it is equal to 5.1±1 km/s and 6.2 ± km/s for the secondary one. The definition of radial velocities of components by LSD profile method and redetermination of spectral orbital elements were carried out. New absolute parameters of components were obtained too.